Percieved Well-Being in Latter Life: A Rural Aging Perspective - Sunuwar, Man Bahadur (Tri-Chandra Journal of Anthropology, 2025)
Rural Nepal's senior population faces numerous challenges, including social isolation, unstable economies, and inadequate access to healthcare. Their QoL, which is impacted by chronic illnesses, disabilities, and financial difficulties, is made worse by insufficient government assistance. The shifting nature of conventional family structures, which were previously an essential source of stability and support, leaves many elderly people, particularly women, vulnerable. The purpose of this study is to identify the perception-related quality of life (QoL) and factors influencing the well-being of senior adults in rural Nepal. A total of 190 participants aged 60 years and above from Chhathar Rural Municipality were surveyed in a quantitative study examining their perception of Quality of Life (QoL) using quantitative methods. The results showed that while individuals living with family and younger seniors (less than 70) reported higher levels of life satisfaction, financial dependency had a detrimental effect on quality of life. Living a single life and the absence of financial support can contribute to dissatisfaction in old age. When needed, older adults sought medical attention, but accessibility was still a problem. The study highlights the value of improved social safety nets, mental health services, and healthcare systems in enhancing the well-being of senior citizens in rural Nepal.